Inclusão social pelo trabalho no contexto da Amazônia Paraense: uma cartografia sobre as conexões, os desencontros e as possibilidades de trabalho decente no campo da saúde mental por meio da economia solidária - Costa, Fabiola da Silva (Universidade Federal de São Carlos, 2025)
People in situations of social disadvantage have historically been marginalized by society. This reality means that many of them have in common the deprivation of basic rights, such as the right to work. Despite the efforts of international regulatory bodies regarding people's access to decent work, the scenario of inequality established at the national level driven by the rise of the neoliberal agenda means that people are inserted into work processes based on exploitation and the deprivation of rights. In the field of mental health, in particular, there is a history of rights violations; people with mental health problems were viewed from the stigma of incapacity and, as a result, were excluded from the world of work. Although remnants of this reality are still present in the social imagination, some Brazilian experiences have materialized as successful practices for social inclusion through the work of these people, most of which have occurred from the perspective of the solidarity economy. In the context of the northern region of Brazil, there are few studies that address the experience of practices of social inclusion through the work of mental health users. The research found indicates that the scenario in which such activities, identified as income generation, occur is within the scope of Psychosocial Care Centers (CAPS). Considering the history of strengthening solidarity economy actions, it is believed that there is a possibility of establishing initial partnerships. In view of this, this study aimed to map the current reality of Solidarity Economic Enterprises (EES) and the experiences of income generation in the field of mental health, alcohol and other drugs, in the Metropolitan Region of Belém (RMB). Seven EES linked to the Rede de Cooperatives Mãos Solidárias (RECOMSOL) and a productive workshop linked to a CAPS AD participated in the study. The cartography method was used, based on the clues of the cartographic method that discusses the four steps of attention of the cartographer-researcher. In this study, they sought to present the paths taken from the initial contact, notes in the field diary, interviews to fill out the forms and implications mobilized in the body of the cartographer-researcher. The first and second parts highlight aspects related to the territory and its implications for the enterprises linked to RECOMSOL and the production workshop. The third part presents data on the profile of the participants, their links with the solidarity economy and mental health, and their forms of marketing and organization. Finally, part four highlights aspects related to possible connections between the solidarity economy network and the production workshop, based on reflections found in the field. Based on the results presented, reflections are presented on social inclusion through work in the context of the Amazon region of Pará, with a view to possible connections through the solidarity economy. It is argued that, as in other regions of the country, the solidarity economy is a powerful instrument for emancipatory actions in the field of mental health. It is expected that more studies will be developed to help us think about processes of social inclusion through work, in the field of mental health, aligned with the reality of the metropolitan region of Belém and Pará. Considering the specificities of being-doing-thinking social inclusion through work of people who use alcohol or other drugs, or not, based on a commitment based on ethical-political action, seeking to guarantee rights, decent work and dignity in life.
Social inclusion through work in the context of the Pará Amazon: a cartography on the connections, mismatches and possibilities of decent work in the field of mental health through the solidarity economy
Keywords: Inclusão social pelo trabalho; Saúde mental; Trabalho; Economia solidária; Social inclusion through work; Solidarity economy; Mental health; Work; Occupational therapy; Terapia ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL